Making Performance Real: Six Paths to Training That Matters - Peterson, Brent D.; Song, Young Hack; Udell, Chuck (Journal of Comparative International Management)

(untitled) (Management Futures, 2019)
Training matters not only for business growth but also for talent acquisition and employee retention. Many experts and researchers highlight the importance and benefits of employee learning and development (Salas et al., 2012). The ATD (Association of Talent Development) 2019 State of the Industry and Training Magazine’s 2019 Training Industry Report indicates that billions of dollars and a tremendous amount of time are being spent on training. Many companies are concerned about the value of their current training programs, especially their leadership development programs (Deloitte, 2018; Kirkpatrick & Kirkpatrick, 2018; Beer et al., 2016; Bernal & Schuller, 2016). As we are experiencing a rapid digital transformation and tough economic times, companies are questioning the effectiveness of their leadership development models. This paper, first, aims to examine seven issues in the learning industry that lead to ineffective training from a practitioner’s point of a view. Then it discusses the Peterson, Song, and Udell (PSU) Training Model, an organizational talent development framework consisting of six specific, focused paths. We also focus on our 4E Training Design Model that resolves issues and makes performance real based on evidence from scientific research and insights from our experiences.